Earnings Persistence in Regulated Industries: The Role of Book–Tax Differences and the Limited Effect of Firm Size - Lutfi, Asep Muhammad; Hajar, Novita (Indonesian Financial Review, 2025)
This study examines earnings persistence in a highly regulated industry by focusing on the role of Book–Tax Differences (BTD) and the limited effect of firm size. Using panel data from Indonesian pharmaceutical firms over the 2014–2024 period, this research incorporates fiscal-accounting dynamics under the post-reform environment of the Harmonized Tax Law. Panel regression analysis with robustness checks is employed to test the proposed relationships. The results show that BTD has a positive and significant effect on earnings persistence, indicating that fiscal reconciliation primarily reflects structured timing differences rather than opportunistic reporting behavior. In contrast, firm size does not have a significant impact, suggesting that industry-specific constraints weaken the conventional relationship between firm scale and earnings stability. These findings highlight the dominant role of fiscal-institutional factors in shaping earnings sustainability, thereby challenging traditional earnings quality perspectives that emphasize firm-level characteristics, particularly in emerging market contexts